Delta-sigma ADC modulator for multibit data converters using passive adder entrenched second order noise shaping - Ali Kareem Nahar; Hussain K. Khleaf (Bulletin of Electrical Engineering and Informatics, 2021)
This paper introduces a multi-bit data converters (MDC) modulator of the 2nd order delta-sigma analog-to-digital converter use the passive adder proposed. The noise shaping quantizer can provide feedback that has generated quantization noise and perform additional shaping noise first-order by coupling noise method.Thus, two Integrator's with ring amplifier and the MDC is shaped by noise coupling quantizer know the 2nd-order noise coupled with somewhat of a DAC modulator. At a summing point, the inputs are summed and then filtered with a low pass filter. A cyclic second order response is generated with a data weighted averaging (DWA) technique in which the DACs ' outputs are limited to one of two states in the noise shaping responses. Mainly as a result of the harmonic distortion in circuits of amplifier. Transistor rate is equipped for the fully differential switched condenser integrator used, a comparator and DWA. The modulator with proposed DWA design, almost quarterly improved timing margin. A simulated SNDR of 92dB is obtained at 20 MHz sampling frequency; while a sinusoidal output of 4.112 dBFS is tested at 90µs besides 20 MHz as the bandwidth. The power consumption is 0.33 mW while the voltage of the supply is 1.2V.